Highlights on International Iran, The Most Important of Which Is The Enjoyment of Economic And Social Activity In Light of The News of The Iraqi Newspaper Al-Jumhuriya 1963- 1968 (Journal of the College of Basic Education, 2025)
The research on the employees and followers of the Brazilian newspaper Al-Jumhuriya, some of whom shed light on Iran’s relations in the economic, sports, social, and cultural fields in the period 1963- 1968 , as Al -Jumhuriya newspaper had a distinguished presence in transmitting and following the news of that country. The news of the Al-Jumhuriya newspaper reported Iran's news and incidents, including what was consistent with the Brazilian government's events from Iran, especially the foreign affairs, during the research period.Al-Jumhuriya newspaper devoted many news and articles to Iranian-Iraqi relations, especially in the political, security, social, sports, and cultural aspects, such as the border agreement in the Shatt al-Arab, cooperation in the fields of education, health, and services, and coverage of the activities of Iranian communities in Iraq and abroad that opposed the Iranian government’s policy at that time. The news and incidents during the research period provided a lot of information that facilitated writing the research. Iranian political relations with the Soviet Union, the United States of America, and Western European countries received an important part of the newspaper’s attention and follow-up. Al-Jumhuriya newspaper can be considered an important source for studying the contemporary history of Iran